Recent Progress of Novel Nanotechnology Challenging the Multidrug Resistance of Cancer - Zhang, Chengyuan; Zhou, Xuemei; Zhang, Hanyi; Han, Xuanliang; Li, Baijun; Yang, Ran; Zhou, Xing (Frontiers in Pharmacology, 2022)
Multidrug resistance (MDR) of tumor is the one of clinical direct reasons of chemotherapy failure. MDR directly leads to tumor recurrence and metastasis, with the extremely grievous mortality. Engineering a novel nano-delivery system for the treatment against MDR tumors have become an important part of nanotechnology. Herein, this review will take the different mechanisms of MDR as the classification standards, and systematically summarize the latest advances in nanotechnology targeting different mechanisms of MDR in recent years. However, it still needs to be seriously considered that there are still some thorny problems in the applications of nano-delivery system against MDR tumors, including the excessive utilization of carrier materials, low drug loading, relatively single targeting mechanism and so on. It is hoped that through the continuous development of nanotechnology, nano-delivery systems with more universal use and simpler preparation process can be obtained, to achieve the goal of defeating cancer MDR and accelerate clinical transformation.